Queen of hearts a novel - Shreve, Susan Richards (Simon and Schuster, 1986)
The beautiful Francesca Woodbine is the granddaughter of a prostitute and fortune-teller, and herself gifted with second sight. She is haunted with guilt and does not realize her own life is in danger.